Phytochemical Profile and In Vitro Bioactivities of Agelanthusdodoneifolius: Antimalarial, Antimicrobial, and Antioxidant Effects (Wudil Journal of Science and Technology Education, 2025)
Agelanthusdodoneifolius (Loranthaceae), a hemi-parasitic plant widely used in NorthernNigerian ethnomedicine for treating malaria, wounds, and infections, was investigated forits phytochemical composition and in vitro bioactivities to validate its traditional uses.Aqueous, chloroform, and ethanol leaf extracts were subjected to qualitativephytochemical screening, revealing the presence of tannins, glycosides, saponins,phenols, and flavonoids, but the absence of alkaloids, anthraquinones, and phlobatannins.In vitro antimalarial activity against Plasmodium falciparum (5% parasitemia) wasassessed using the Giemsa staining method, with chloroform and ethanol extractsexhibiting dose-dependent activity. The chloroform extract achieved 84.7% parasiteelimination at 10 mg/mL after 48 hours, significantly higher than the ethanol extract(82.4%, p = 0.0145), though less potent than artemether (92.7%). Antimicrobial activitywas evaluated via the broth microdilution method against Staphylococcus aureus (ATCC25923), Escherichia coli (ATCC 25922), and Candida albicans (ATCC 10231), withminimum inhibitory concentrations ranging from 0.625 to 5 mg/mL for ethanol extractsand 1.25 to 10 mg/mL for chloroform extracts, supporting traditional uses for woundhealing. Antioxidant activity, assessed by the DPPH assay, showed IC₅₀ values of 0.45 ±0.03 mg/mL (ethanol) and 0.82 ± 0.05 mg/mL (chloroform), indicating significant radicalscavenging potential compared to ascorbic acid (0.02 ± 0.01 mg/mL). These findingsvalidate the ethnomedicinal applications of A. dodoneifolius and highlight its potential asa source of antimalarial, antimicrobial, and antioxidant agents. Further studies arewarranted to isolate bioactive compounds, elucidate mechanisms of action, and assess invivo efficacy and ecological sustainability for therapeutic development.
Keywords: Agelanthusdodoneifolius, hemi-parasitic plant, phytochemical composition, in vitro bioactivities, malaria, wounds, infections, phytochemicals.